Development of the social burnout scale for college students - Wang, Jing; Liu, Chang; Chen, Longling; Liao, Qiuyue; Liu, Guoqin (Frontiers in Psychology, 2024)
Although fruitful achievements have been explored about job burnout, little is known about burnout in the field of social interaction among college students. To address this limitation, this study defined the concept of Social Burnout and developed a measurement tool for it. The study adopted the method of combining qualitative research with quantitative research. After the qualitative study, we gathered examples of social burnout and finished item writing. Using convenient sampling and theoretical sampling methods, six different samples were recruited for reliability and validity testing. Confirmatory factor analysis (CFA) revealed the scale’s two-factor structure: emotional exhaustion and depersonalization. Cronbach’s alpha measured the internal consistency of the social burnout scale (SBS), which was excellent (Cronbach’s alpha of emotional exhaustion = 0.94; depersonalization = 0.82; the overall = 0.92). Susequently, the method of calculating AVE and CR evaluated the scale’s convergent and discriminant validity, which were relatively good (AVE of emotional exhaustion = 0.60, depersonalization = 0.59; CR of emotional exhaustion = 0.93, depersonalization = 0.81). Then, regression analysis verified the nomological network and criterion-related validity (r = −0.30, p < 0.01; r = −0.39, p < 0.01; β = −0.25, p < 0.01). The SBS was shown to be a reliable and appropriate measure for assessing students’ social burnout. Furthermore, the SBS is recommended for use in academic research and by healthcare professionals to measure students’ social distress. Further validation studies of this scale are needed in other cultural contexts.